Main directions of implementing research results of artificial intelligence systems into domestic production - F. F. Sharipov; M. A. Dyakonova (Вестник университета)
Speaking about the need to create technological sovereignty in the sphere of the domestic economy production, we realize how multidimensional and costly in all types of resources is the activity that has critical time constraints. In addition to sovereignty as a concept in the broad sense, technological sovereignty is created to increase the efficiency of Russian economic activity. One of the directions of increasing the production activities efficiency is the so-called production digitalization. This notion is fundamentally different from the production processes automation of the 1970s and 1980s. With the advent of the Internet and space navigation capabilities of modern astronautics, the approach and level of tasks in organizing human life have completely changed. Wireless communication, the Internet of Things, unmanned vehicle including aircraft are the terms of the XXI century. The purpose of the study is to define the theoretical principles of digitalization in the manufacturing process for those who are interested in this issue. The authors also attempt to provide a summary of popular classifications of digital technologies by functionality and application sectors. Based on the theoretical principles of digitalization and the given classification, we identify the main directions of production digitalization.